IMPLEMENTASI ITILV4 FRAMEWORK IT ASSET MANAGEMENT PRACTICE PADA PT. INTEGRASI DATA NUSANTARA - Pratama, Ferry Fajar; Mulyana, Dadang Iskandar (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Asset management is an important process that must be carried out by a company in managing its assets effectively and efficiently. PT. Integrasi Data Nusantara is a company that requires good asset management in carrying out its business operations. Therefore, the authors conducted research on the implementation of asset management practices at PT. Integrasi Data Nusantara using the ITILv4 framework. This study aims to identify the steps that must be taken in implementing asset management practices at PT. Integrasi Data Nusantara using the ITILv4 framework and providing recommendations regarding improvements that can be made. This study uses a qualitative descriptive method by conducting interviews with several respondents who are involved in the implementation of asset management practices at PT. Integrasi Data Nusantara. The author then makes a GAP analysis which will be used as a reference for the implementation of ITILv4 IT Asset Management practices. Based on the results of the questionnaire that has been carried out, the researcher found that the implementation that has been carried out has produced positive results for IT asset management at PT. IDN. This is shown by the results of a survey using a Likert scale which has an average value of 4 on a Likert scale of 1-5.